2017
DOI: 10.1080/15321819.2017.1319860
|View full text |Cite
|
Sign up to set email alerts
|

ALK protein expression in pulmonary adenocarcinoma of Tunisian patients

Abstract: The frequency of positive ALK expression based on immunohistochemistry in our series was similar to that reported in the world literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
2
1
Order By: Relevance
“…23,24 However, the rate is lower than those of 7.1% and 7.8% recorded in Spain and the USA, respectively, 19,20 as well as rates of 5% and 9% in two earlier Tunisian studies. 25,26 In line with most previous reports 5, [21][22][23][24]34 we found that ALKpositive patients were significantly younger than those with ALK-negative tumors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…23,24 However, the rate is lower than those of 7.1% and 7.8% recorded in Spain and the USA, respectively, 19,20 as well as rates of 5% and 9% in two earlier Tunisian studies. 25,26 In line with most previous reports 5, [21][22][23][24]34 we found that ALKpositive patients were significantly younger than those with ALK-negative tumors.…”
Section: Discussionsupporting
confidence: 90%
“… 23 , 24 However, the rate is lower than those of 7.1% and 7.8% recorded in Spain and the USA, respectively, 19 , 20 as well as rates of 5% and 9% in two earlier Tunisian studies. 25 , 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency that we found falls globally between the frequencies reported in whites and those reported in Asians [9][10][11][12][13][14]. However, it's lower than the frequency found in two previous Tunisian studies that reported an ALK rearrangement frequency of 5.2 and 9.09%, respectively [15,16] (Table 4).…”
Section: Discussioncontrasting
confidence: 60%